Transformational leadership and its role in enhancing digital transformation among Omani teachers in light of Oman Vision 2040 - Al-Buraiki, Ali Hamad Salem; Belaid, Youssef Nait (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the role of transformational leadership in enhancing the digital transformation of Omani teachers in light of Oman Vision 2040. The school community of all 911 public school leaders in the Sultanate of Oman, and the study sample included (263) individuals. The study adopted a descriptive approach as a methodology and used a questionnaire as a tool. The study found that the role of transformational leadership in enhancing the digital transformation of Omani teachers in light of Oman Vision 2040 was at a (medium) response level. The study recommended setting a clear and inspiring vision for the digital future of education, linking it to the goals and priorities of Omani teachers, and building trust and respect between leaders and teachers through open and honest communication and active participation.